A Review on the epidemiology of spine injuries in golf players - Heyman Mohammadi; Mohammad Hosein Alizadeh; Elham Shirzad (Vesnu Publications, 2013)
Abstract Introduction: Golf is a popular sport played worldwide for wich there is no sex and age limit and also no extreme strength or flexibility requirements. The  incidence  of  golf  injuries  has  received  little  attention  in  the  literature .The diversity of the ages and abilities of golf players leads to a wide spectrum of injuries. However, there is a paucity of data regarding golf injuries. Therefore, the aim of this study was to review the epidemiology of spine injuries in golf players. Materials and Methods: Searching in specific scientific citations was carried out for relevant articles with the subject coverage of golf injuries, spine injuries and golf spine injuries from 1982 to 2011. Results: Results showed that the prevalence of the total body injuries in golf was 42.3%. The most common site of injuries was lower back (18.3% to 31.5%) with an average of 26.2%. The incidence of spinal cord injury was 39.4% that indicates the high prevalence of spinal injuries in this sport. The average percent of lower back injuries in golf is 33%. The most commonly reported site of injury was lower back in men and forearm and elbow in women. Moreover, the low back pain was somewhat more common in men than in women. Comparing professional and amateur athletes, low back pain was more common in professionals. Conclusion: Lower back is the most common site of injuries in golf. The main causinig mechanism of such injuries may be the overuse of incorrect swings. To prevent lower back injuries, it is recommended that amateur golf players attempt to learn correct swing movements. Coaches of professional golf players may also focus on the core stability exercises in order to minimizing the likelihood of lower back injuries. Keywords: Epidemiology, Golf Spine Injury, Golf Swing